High-fat Diets Containing Soybean or Canola Oil Affect Differently Pancreas Function of Young Male Rats - da Costa, C. A. S.; Carlos, A. S.; de Sousa dos Santos, A.; de Moura, E. G.; Nascimento-Saba, C. C. A. (Hormone and Metabolic Research, 2013)
The excessive fat intake generally might induce obesity and metabolic disturbances. Thus, the goal of the study was to assess the role of high-fat diets containing soybean or canola oil on intra-abdominal adiposity and pancreatic morphology and function of young rats. After weaning, rats were fed with a control diet (7S) or a high-fat diet containing soybean oil (19S) or canola oil (19C) until they were 60 days old, when they were sacrificed. Food intake (g/day), body mass and length, retroperitoneal and epididymal fat mass, HOMA-IR, HOMA-β and area of pancreatic islets were assessed. The results were considered different with a significant level of p<0.05. Both 19S and 19C groups showed higher body mass, length, and retroperitoneal fat mass. The 19C group showed higher HOMA-IR (+43% and +78%) and HOMA-β (+40% and +59%) than 19S and 7S groups, respectively. Both 19S and 19C groups showed lower pancreatic islets area in relation to 7S group. Meantime, 19C presented lower percentage of pancreatic islets area in comparison to 19S (−41%) and 7S group (−70%, p<0.0001). Independent of soybean or canola oil, the high fat diet promoted development of the obesity. Comparing 19C and 19S groups, the higher concentrations of monounsaturated fatty acids, present in the canola oil were worse than higher concentrations of polyunsaturated fatty acids, present in the soybean oil.
Keywords: nutrition; obesity; insulin